Enhancing the Economy and Human Capital of Santri Through Education: The Role of Islamic Boarding Schools (Dayah) in Aceh - Yunus, Mukhlis; Long, Ahmad Sunawari bin; Faisal, Faisal; Nizam, Ahmad; Jalaluddin, Jalaluddin; Sakir, A; Riyaldi, Muhammad Haris; Adam, Muhammad; Musnadi, Said; Mahdani, Mahdani; Kesuma, Teuku Meldi; Siregar, Muhammad Ridha (Jurnal Pengabdian Bakti Akademisi, 2025)
The rapid advancement of globalization has made economic and human resource (HR) development a key driver of national progress. Education plays a pivotal role in improving quality of life and economic welfare, particularly within thedayah(traditional Islamic boarding school) communities in Aceh. As Islamic educational institutions, dayah hold significant potential in educating and empowering local communities. However, challenges such as limited infrastructure, lack of access to modern technology, and insufficient skill development programs remain major obstacles. To address these issues, innovative approachesincluding vocational training and entrepreneurship educationmust be strengthened and integrated into the dayah curriculum. Collaboration with local industries and training institutions can provide market-relevant skills development.Community service initiatives conducted at Dayah Mini Aceh, which focus on enhancing economic and HR capacities through education, have demonstrated significant outcomes. Evaluations reveal improved understanding and skills among santri (Islamic students) in leveraging education to boost economic well-being. These efforts also contribute to achieving the Sustainable Development Goals (SDGs), particularly in quality education (SDG 4) and decent work (SDG 8). This article provides a comprehensive overview of the challenges faced by dayah and proposes innovative solutions to transform them into effective hubs for education and economic empowerment. By addressing systemic barriers and fostering strategic partnerships, dayah can play a vital role in advancing both local and national development agendas.